Repetition Compulsion in the Character of Sonny Hayes in “F1: The Movie” (2025): A Psychoanalytic Study - Dika Romadhona Wahyu Slamet Budi Kusuma; Titis Setyabudi (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2026)
This study examines the representation of repetition compulsion in Sonny Hayes, the protagonist of “F1: The Movie” (2025), whose persistent return to dangerous racing despite past trauma exemplifies an unresolved psychological pattern rarely examined in film scholarship. While prior studies have addressed trauma recovery or applied alternative frameworks such as logotherapy to fictional characters, none has combined Freud's repetition compulsion with Todorov's narrative theory to analyze how this specific psychological condition is structurally embedded within a film's plot. This study addresses that gap by synthesizing Freud's psychoanalytic theory of repetition compulsion with Todorov’s narrative stages, creating a dual-framework approach to analyze how psychological pathology is structurally encoded in cinema. By mapping four clinical forms of compulsion such as unconscious drive, reenactment, connection to trauma, and attempt at mastery, onto the film's five-stage plot progression, the research demonstrates that character behavior is not merely a plot device but a systematic representation of unresolved psychic wounds. The findings identify four forms of repetition compulsion unconscious drive, reenactment of painful experiences, connection to trauma, and attempt at mastery structurally organized across Todorov's five narrative stages. This study contributes a specific analytical model for tracing psychoanalytic conditions through narrative structure, offering a concrete reference point for future studies examining repetition compulsion in other film characters.